Context-mechanism-outcome configurations in the admissions programs of Philippines higher educational institutions - Estacio, Lexie C. (College of Education, University of the Philippines Diliman, 2021)
Realist evaluation (RE) has been proven as a strategic lens in understanding interventions or social programs as reflected in literature and evaluation studies. As one of the most important components of an educational institution, the Admissions Office (AO) carries out the screening and selection criteria in accepting applicants to the respective academic degree programs. The study is a RE of the Admission Programs (APs) of three private and three public universities in Luzon, Visayas, and Mindanao. Consistent with the RE methodology, the first phase of the evaluation was the identification of the program theory underlying the AP. Afterwards, qualitative and quantitative data were gathered to identify the contexts, mechanisms, and outcomes (CMO) of the APs. These were subjected to an iterative process of coding. Multiple sources of data were used to generate the CMO configurations: (1) a review of literature on the functions, objectives, processes, and operations of the admissions program and office in HEIs, (2) survey questionnaires administered among first and second year students in public and private HEIs, and (3) interviews with the key officials and staff involved in the work of admissions. To facilitate and deepen the analysis, contexts were categorized into Internal and External. The intersecting and distinct internal and external contexts of the public and private HEIs were likewise examined. Mechanisms, on the other hand, were classified as either Positive or Negative. The process of grouping together the contexts and mechanisms was iterated to ensure that data were categorized accordingly. Once these were in place, the successful and unsuccessful program outcomes (enrollment and student attrition) identified by the key officials involved in the work of admissions, guided the phase of configuring the CMOs. Table were prepared to group the coded contexts and mechanisms that emerged from the responses and insights of the three groups of program stakeholders (student, faculty members, and admissions officials). This enabled the configuration of the relevant contexts and mechanisms to the most appropriate program outcomes (enrollment or student attrition). After closely examining the CMO tables, the final CMO configurations focused on the three groups of stakeholders that participated in the study, namely, students, faculty members, and admissions team members. This allowed the presentation of specific ways on how each CMO configuration could benefit the three groups of stakeholders. Nine (9) CMO configurations were generated. Two (2) are directed to students which are as follows: (1) The admissions office's accessibility, clear and fast procedures, reasonable acceptance criteria, and friendly and helpful staff (C), make the students happy and satisfied (M) which eventually lead to their enrollment in the university (O) and (2) Strong recommendation from family and friends (C1) and from high school teachers/guidance counselors (C2) help increase HEIs enrollment (O) since theses build students' confidence in the university (M). The two (2) CMO configurations that focus on faculty members are (1) If faculty members are familiar with the admissions criteria and procedures (C), their expectations as regards the academic capability of their students are better addressed (M). This helps them manage their students academically and personally which contribute to the attainment of low student attrition rates (O) and (2) Faculty members' confidence in the ability of admissions office to attract the best students is strengthened (M) when they are given opportunities to contribute to the improvement of the admissions program (C) to increase enrollment (O1) and to minimize student attrition rates (O2). The CMO statements that correspond to the admissions team are as follows: (1) Competition with big and well-established universities (C1) together with the implementation of the free tuition in tertiary education in public HEIs (C2) pressure on the admissions team (M) to achieve the target enrolment (O), (2) Increase in enrollment (O1) that is attributed to the absence of admissions criteria in private universities (C) result in HEIs' Management's satisfaction (M) and at the same time eventual increase in student attrition rates (O2), (3) Admissions team in private universities are challenged to solve (M) withdrawals of enrollments due to financial reasons and failure in meeting student expectations (C) since these contribute to high student attrition rates (O), (4) Strong support from the management (C) motivates the admissions team (M) to aim for high student enrollment (O), and (5) The involvement of the alumni in the work of admissions (C) becomes a motivation to give back to their alma mater by initiating programs and activities (M) that help increase the institution's enrollment (O). Conclusions and recommendations based on the finding were presented to provide a better understanding of the APs. This is specifically intended to support the HEIs in refining their admissions processes and systems to provide program outcomes. Lastly, it is recommended that researchers conduct similar studies using the RE methodology in different groups or settings for the testing and refinement of the CMO configurations. This will also expand the limited literature on RE in the field of education.